Biosafety of Forest Transgenic Trees Improving the Scientific Basis for Safe Tree Development and Implementation of EU Policy Directives - Vettori, Cristina; Gallardo, Fernando; Häggman, Hely; Kazana, Vassiliki; Migliacci, Fabio; Pilate, Gilles; Fladung, Matthias (Forestry Sciences, 2016)
This book provides up-to-date information on the environmental impact of transgenic trees on genetically modified tree (GMT) communication strategy. It is useful to public/private organisations as well as to private and public research bodies and universities worldwide since it reports on the global status of GMT research and policy. A high number of genetically modified trees (GMTs) with altered or novel characteristics have been produced in the last 15 years. However, their very low public acceptance is a basic problem in their commercialization. Breeders anticipate economic and ecological benefits, like reduced product costs and less pressure on native forests, while opponents fear risks, such as unintended spread of GMTs. But what is true? To answer this question, the COST Action FP0905 focused on key aspects related to GMTs: (a) biological characterization; (b) assessment of possible environmental impacts; (c) socio-economic implications and public acceptance/concerns; (d) providing science-based information to communicate with the public.